2019
DOI: 10.1016/j.bar.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Country-level corruption and accounting choice: Research & development capitalization under IFRS

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 102 publications
3
39
0
2
Order By: Relevance
“…Thus, high-quality accounting practices can enable incumbent politicians to better demonstrate political accountability, so as to be able to fend off the attacks of competing politicians [1,9,65]. From credible and transparent financial information, the potential for corruption can be monitored early, so that it can focus on investments to increase economic growth [2,8,24].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, high-quality accounting practices can enable incumbent politicians to better demonstrate political accountability, so as to be able to fend off the attacks of competing politicians [1,9,65]. From credible and transparent financial information, the potential for corruption can be monitored early, so that it can focus on investments to increase economic growth [2,8,24].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…High-quality accounting practices can increase the credibility of financial information through the presentation of financial reports on a regular and timely basis so as to increase transparency and accountability in the public sector, and have an impact on reducing corruption [32][33][34]. At present several studies focus on the relationship between accounting practices and corruption [1,2,24,35], with overall results showing that reducing corruption can be done by the state countries with high quality accounting practices compared to countries with low quality accounting practices.…”
mentioning
confidence: 99%
“…Corruption in Indonesia is in danger position. Corruption practices in Indonesia are increasing from year to year, both of the state's financial losses and increasingly systematic quality, more sophisticated and relevant in all aspects of society (Mazzi et al, 2019). The increase in corruption is uncontrolled.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the level of investor protection is more important than governance mechanisms in enhancing the relation between R&D and performance. At the same context,Mazzi et al (2019) used the time lag of five years for future earnings and they found a positive relationship between R&D and firm performance.…”
mentioning
confidence: 99%
“…In addition,Ahmed and Falk (2006) found that companies that capitalize R&D expenditures have higher market share price compared to companies that expense R&D expenditure. Moreover,Mazzi et al (2019) found that in countries with high corruption level, managers choose to capitalize R&D expenditures compared to expensed it, and this treatment is reflected on future performance.At the same context,Ali et al (2012) analyzed the effect of the accounting treatment for R&D expenditures as period expenses. They found that this treatment affects investors and stock analysts' evaluation for future returns, which leads to lower estimation and lower stock price.…”
mentioning
confidence: 99%